Boosting the sodium storage of the 1T/2H MoS2@SnO2 heterostructure via a fast surface redox reaction. Issue 1 (15th December 2020) - Gui, Dayong; Wei, Zhijie; Chen, Jian; Yan, Liwei; Li, Jun; Zhang, Peixin; Zhao, Chenyang
Abstract : Ultrasmall SnO2 nanoparticles distributed on dual phase MoS2 sheets boost the Na + storage kinetics via a fast surface redox reaction. Abstract : The sluggish kinetics and large volume expansion arising from the large ionic radius of Na + remain elusive weaknesses of sodium ion batteries (SIBs). Here, we report a transition from bulk diffusion to surface-dominant pseudocapacitive charge storage by nanoscaling and heterostructuring, which enables fast and stable charge storage kinetics for SIBs. An electronic attraction induced self-assembly strategy was developed for the synthesis of the 1T/2H MoS2 @SnO2 heterostructure. Ultrasmall SnO2 nanoparticles with a low crystallinity were uniformly distributed on the basal plane of MoS2 . The intercalated SnO2 serves as an interfacial pillar to restrict the restacking of MoS2 nanosheets, whereas dual-phase 1T/2H MoS2 provides a continuous network for efficient charge transfer and restrains the aggregation of Na x Sn. As a result, the 1T/2H MoS2 @SnO2 heterostructure exhibits a higher specific capacity (626 mA h g −1 at 0.1 A g −1 ), and superior cycling and rate capabilities (262 mA h g −1 at 2 A g −1 for 500 cycles) compared to the raw MoS2 and 2H MoS2 @SnO2 counterparts. Electrochemical kinetics analyses reveal that the charge transfer kinetics are boosted by the synergistic effect between the 1T/2H MoS2 and SnO2 nanoparticles. Quantitative examination into the origin demonstrated that the Na + storage is dominated by the fast surface redox reaction, which endows the heterostructure with a durable high rate capability.